2018
DOI: 10.1017/s1368980017003792
|View full text |Cite
|
Sign up to set email alerts
|

Declaration of nutrition information on and nutritional quality of Thai ready-to-eat packaged food products

Abstract: The findings suggest effective policies should be implemented to increase the relative availability of healthier ready-to-eat packaged foods, as well as to improve the provision of nutrition information on labels in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…This can be partly explained by the high prevalence of fast-food chain restaurants in Asia. Thailand, as a middle-income country, has been considered a new market for penetration by the processed food industry [20], which provides a greater supply of and increases the demand for fast foods and beverages [21]. Indeed, the traditional Thai food culture has changed dramatically, and Thais now follow fashion/trends in food consumption [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be partly explained by the high prevalence of fast-food chain restaurants in Asia. Thailand, as a middle-income country, has been considered a new market for penetration by the processed food industry [20], which provides a greater supply of and increases the demand for fast foods and beverages [21]. Indeed, the traditional Thai food culture has changed dramatically, and Thais now follow fashion/trends in food consumption [2].…”
Section: Discussionmentioning
confidence: 99%
“…Western-style fast-food consumption is playing an increasingly important role in the Thai food culture [2]. Therefore, although key actions have been taken by the Thai government, such as nutritional labelling, providing nutrition claims [20], and the use of Guideline Daily Amounts [20,21], these actions appear to be inadequate.…”
Section: Discussionmentioning
confidence: 99%
“…By coding claims using the standardized approach outlined by INFORMAS [44,48], comparisons are now feasible. This analysis showed that overall food labels in Canada are more heavily marketed (i.e., prevalence of nutrition marketing) (52%) than in New Zealand (39%) [51], Slovenia (39%) [29], the UK (32%) [52], five European countries (26%) [50], and Thailand (25%) [53], although Canada showed similar proportions to Australia (56%) [27]. However, in many of those countries other nutrition regulations are already in place to restrict the use of nutrition marketing on foods with an “unhealthy” nutritional profile; for example, through the use of nutrient profiling models to determine if a food is eligible to carry certain claims [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…The INFORMAS taxonomy is an internationally standardized methodology for the collection and comparison of nutrition-related marketing on packaged foods and beverages [44]. The purpose of using the INFORMAS taxonomy was two-fold: to allow objective comparison with similar studies that have investigated nutrition marketing in the food supply worldwide [27,29,50,51,52,53], and to minimize bias towards identification of other label components that are not currently mandated in Canada (e.g., supplementary nutrition information and quantitative ingredient declaration). This taxonomy divides nutrition-related labelling on food packages into the following two components: (1) nutrition information and, (2) nutrition and health claims [48].…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient content claims (NCCs) are those that “describe the amount of a nutrient in a food”, and some examples include “excellent source of calcium” or “low in sodium” [ 1 ]. Although nutrient content claims are the type of claim most often used on food labels worldwide as well as in Canada [ 2 , 3 , 4 , 7 , 9 , 11 , 22 ], products bearing such claims are not always indicative of higher nutritional quality [ 3 , 6 , 11 ]. Health claims are “any representation in labelling or advertising that states, suggests, or implies that a relationship exists between consumption of a food or an ingredient in the food and a person’s health” [ 21 , 23 ], and comprises two subtypes: disease risk reduction claims (which are statements that link a food or constituent of a food to reducing the risk of developing a diet-related disease or condition; for example, “a healthy diet rich in a variety of vegetables and fruit may help reduce the risk of some types of cancer”) and nutrient-function claims (which describe the well-established roles of energy or nutrients that are essential for the maintenance of good health or for normal growth and development; for example, “This product is a source of calcium.…”
Section: Introductionmentioning
confidence: 99%